Power Relations Within Patriarchal Society in the Film Enola Holmes - bintang priyanto putri; Rahayu Puji Haryanti; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
The Enola Holmes film is a kind of film that mostly talks about patriarchal society, oppressions, stereotypes, and women’s power. This paper explores the power relations and patriarchal society portrayed in the film Enola Holmes. This research used a qualitative method focusing on dialogues and scenes that contained power relations and patriarchal society from Enola Holmes's film script. Using the Critical Discourse Analysis (CDA) of Norman Fairclough and the power relations of Michel Foucault, I analyze the relation between patriarchal society and the power relations portrayed in the film. The finding of the data analysis showed that the discourse produced in this film script is that patriarchy is a very bad thing, and thus, it should be banished. Thus, women should be given more room and space in society.